The Politics of the Past - Dezhamkhooy, Maryam (Archaeopress, 2019)
This book examines the highly problematic politics of the past surrounding the archaeology of ancient empires in Iran. Discussing their personal and professional experiences, the authors exemplify the real, ethical dilemmas that archaeologists confront in the Middle East, calling for reflectivity and awareness among the archaeologists of the region.